A Study on the Middle Manager Managerial Core Competencies and Training Requirements in Local Government - Chang, Jen-Chia; Ou, Chingyu (Advances in Social Sciences Research Journal, 2022)
The “Chief” of local government is a middle manager within the organization. This role is responsible for the communications and implementation of various policies of the county and city governments externally. Internally, the role is responsible for team building and giving work directions. If it is possible to cultivate the person to become a “knowledge worker” through trainings, this can strengthen one’s job competency and effectively enhance the agency’s administration performance. Public service with better quality can be provided. This study adopts the “survey techniques.” The survey is based on the “managerial core competency items of the mid and high-level management positions in the agencies under the Executive Yuan.” There are 6 items of core competency aspects (problem analysis, project management, performance management, information management, communications and coordination, and team building) established and there are 16 items as basic competencies. Testing is applied to the middle manager, the director and deputy director and chief of staff of the service units of the K City government based on the survey highlights. It is hoped to discuss the managerial core competencies and their training requirements for the middle manager of the local government. The purpose is to enhance the competency at the job in order to strengthen the managerial core competency of the middle manager of the City government. Thank you to K City government for authorizing the use of the original data of the above survey. Based on the research results, it has been confirmed that the Junior rank civil service middle manager established by the Executive Yuan, its managerial core competency items are applicable to local government. Under training resource constraints for the agencies, the trainings for the middle managers of the local government shall be prioritized and strengthened based on the needs: They are competencies in “performance expression and communications” and “job motivation” and continue to maintain the 7 core competency items in “problem identification,” “program planning,” “communication expression,” “conflict management,” “job instruction,” “team management” and “knowledge management.”